Scope and Common Diseases of Rural Poultry Production by Rural Women in Selected Villages of Kwara State, Nigeria - Adebayo , S.A.; Ogunlade, I.; Fayeye, T.R. (International Journal of Poultry Science, 2013)
This study was carried out to determine the scope of poultry production by rural women and common diseases associated it in selected Local Government Areas of Kwara State, Nigeria. Specifically, the study examined various parameters of poultry production, the time of the year that diseases were most observed, the rate of mortality associated with various diseases and level of vaccination of birds in those villages. One hundred and twenty (120) women involved in rural poultry production were randomly sampled from four (4) villages in Kwara State, Nigeria. Interview schedule was used to elicit information for the study. The data were analyzed and presented as frequency counts and percentages. It was discovered that rural poultry production was still at the subsistent level. The highest percentage of the women involved in rural poultry production had 1-10 bird(s) per species (59.13, 71.43 and 57.14% for chicken, duck and guinea fowl respectively). A larger percentage of chicken (76.72%) hatched between 1-10 bird(s) per laying period while ducks hatched more birds than chicken during each laying period (65% hatched between 11 and 20 birds). Guinea fowls had almost an even spread of the number of birds hatched per laying period across the flock size ranges considered. The common diseases observed by the respondents include Newcastle disease, fowl pox, coccidiosis and infectious bursal disease. The time of the year that diseases were prevalent was between September and December. Newcastle disease was indicated as the disease that resulted in the highest in mortality rate. Majority of the respondents had never vaccinated their birds and very few have ever contacted veterinary services (5-10%), except at Share (63.33%). It is therefore recommended that knowledge of rural women on poultry production should be improved. It is therefore recommended that awareness campaign should be conducted in the villages on how they can increase their rural poultry productivity, alerting them of the causes of various diseases and the available remedy.